PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA BADAN PERTANAHAN NASIONAL (BPN) KOTA BANDUNG - Rachnat Nugraha, - (2012)
This research was conducted on Badan Pertanahan Nasional (BPN), Bandung employees. This research aims to determine the influences of Compensation And Motivation of The Employee's Performance On Badan Pertanahan Nasional, Bandung either partially or simultaneously. Issues that examined in this research is about how the image forms of compensation awarded, image of the level of motivation to work, image of employee performance, how much influence on the performance of compensation and motivation of the employee either partially or simultaneously. Aspects that examined in this research include in three things, namely compensation, motivation and employee performance. Indicators used for the variable compensation is salary, transport allowance, overtime pay, honoraria money activity, pension, clothing services, job promotion. Indicators used for variable motivation is creativity, feedback, taking into account efficacy, together with the tasks, influence and control others, the response against each organizational problems, the need for feeling accepted by others in the workplace, the need for feeling excluded. Whereas indicators of employee performance is the quality of work, quantity of work, reliability, discipline, and attitudes toward other employee. This research uses explanatory survey methods, data collection techniques by means of literature studies, field studies and dissemination of questionnaires. Instrument used was a questionnaire with Likert-scale model of data analysis used is a simple regression analysis and multiple regression. Number of members of a population is 126 people, then the sample is taken using simple random sampling of 60 people the criteria for rejection of the hypothesis, showing that H0 is rejected and H1 is accepted. Regression coefficient between variables X1 and Y if confirmed by the criteria of rejection of the hypothesis, showing that H0 is rejected and H1 is accepted. Regression coefficient between variables X2 and Y if confirmed by the criteria of rejection of the hypothesis, showing that H0 is rejected and H1 is accepted. Regression coefficient between variables X1 and X2 if confirmed by the criteria of rejection of the hypothesis, showing that H0 is rejected and H1 is accepted. Of the results showed that Compensation has a positive effect on the performance of Badan Pertanahan Nasional, Bandung. Motivation has a positive effect on the performance of Badan Pertanahan Nasional, Bandung. Compensation and Motivation has a positive effect on the performance of Badan Pertanahan Nasional, Bandung.